Archaeological perspectives on warfare on the Great Plains - Clark, Andrew J., editor; Bamforth, Douglas B., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
Anthropologists from across the Plains critically examine regional themes of warfare from pre-Contact and post-Contact periods and assess how war shaped and reflected human societies on the Plains. Brings together research from across the region, provides unprecedented evidence of the effects of war on tribal societies.--Provided by publisher.
What do we know about warfare on the Great Plains? / Douglas B. Bamforth -- Northwestern Plains contact-era warfare as reflected in ethnohistory and rock art studies / Mavis Greer and John Greer -- Warriors and weapons: late prehistoric/protohistoric -- period warfare in Bear Gulch rock art / James D. Keyser -- Coup counts and corn caches: contact-era Plains Indian accounts of warfare / Linea Sundstrom -- Rotten palisade posts and rickety baffle gates: fortifying native eastern North America / David H. Dye -- Ditches or earthworks: a reexamination of fortified villages on the Upper Missouri River / Albert M. LeBeau, III -- Why fortify: force-to-force ratios and fortification on the Southern Plains / Susan C. Vehik -- Digging ditches: archaeological investigations of historically reported fortifications at Bryson-Paddock (34KA5) and other southern Plains village sites / Richard R. Drass, Stephen M. Perkins, and Susan C. Vehik -- The Alcova Redoubt: a refuge fortification in central Wyoming / Bryon Schroeder -- Conflict and culture change on the Plains: the Oneota example / R. Eric Hollinger -- Modeling Middle Missouri warfare / Mark D. Mitchell -- Alliances, clusters, and spatial analysis: a multiscalar approach to studying warfare in the Middle Missouri / Andrew J. Clark -- The Crow Creek massacre: the role of sex in Native American scalping practices / Ashley Kendell -- Contexts for conflict: conceptual tools for interpreting archaeological reflections of the North Platte campaign of February 1865 / Peter Bleed and Douglas Scott -- Afterword: war, peace, and plains archaeology / Douglas B. Bamforth and Andrew J. Clark.
Keywords: Indians of North America -- Wars -- Great Plains; Indians of North America -- Warfare -- Great Plains; Indians of North America -- Great Plains -- Antiquities; Excavations (Archaeology) -- Great Plains